Depression, anxiety and stress during the health emergency due to Covid-19, in head of household residents in a Human Settlement in Comas - Millones-Morales, Patricia Elizabeth (2021)
Objectives: To determine depression, anxiety and stress during the health emergency due to COVID-19, in heads of households residing in a human settlement in Comas. Materials and methods: This study with a quantitative approach, descriptive-cross-sectional design. The population was made up of 115 resident heads of household. The technique used was the survey and the measurement instrument was the Generalized Anxiety Disorder Scale (GAD-7), which is made up of 21 items and 3 dimensions, which are: depression, anxiety and stress. Results: Regarding age, the minimum was 17 and the maximum was 85, with the mean age being 41.31. Regarding sex, 59.1% (n = 68) are female and 40.9% (n = 47) male. Regarding the psychological impact during the health emergency due to COVID-19, in resident heads of households where extremely severe prevailed with 41.7% (n = 48), followed by moderate in 20.9% (n = 24), mild with 20% (n = 23), normal and extremely severe in 8.7% (n = 10). In relation to the dimensions, in depression the moderate level was more prevalent with 27% (n = 31), in anxiety the moderate level with 17.4% (n = 20) and in stress the severe level with 25.2% (n = 29). Conclusions: In this study they conclude that the psychological impact predominated at the extremely severe level, followed by moderate, mild, normal and extremely severe. Regarding the dimensions, all the extremely severe level predominated and in stress the normal level.